ACUTE OBSTRUCTIVE INTESTINAL OBSTRUCTION IN CHILDREN: DIAGNOSIS, TREATMENT, AND PREVENTION METHODS (Herald of the National Children's Medical Center, 2025)
Acute adhesive intestinal obstruction (AIO) is a serious postoperative complication observed among children. The main causes of its development include acute appendicitis, intestinal perforation, and developmental anomalies. The disease is associated with the formation of adhesions between the peritoneum and intestines, leading to impaired intestinal patency. There are challenges in diagnosis, and the development of effective treatment methods remains an urgent issue.
Keywords: adhesive intestinal obstruction; children; delayed diagnosis; conservative treatment; laparoscopic surgery; intestinal adhesions